SPATIAL DISTRIBUTION OF SACHET WATER BRANDS IN KADUNA METROPOLIS, KADUNA STATE, NIGERIA - Habila, M. I.; Dadan-Garba, A.; Daful, M. G.; Helda, B. S.; Lawal, N.; Onwumere, G. B.; Vincent, C. U.; Yabo, S. D. (FUDMA Journal of Sciences, 2025)
The sachet water industry has become a major source of drinking water in Nigeria due to the inadequacy of public water supply systems. This study investigates the spatial distribution of registered sachet water factories in Kaduna Metropolis, Kaduna State, Nigeria. Using data from the Standards Organization of Nigeria (SON) and the National Agency for Food, Drug Administration and Control (NAFDAC), the 554 registered sachet water brands were captured combined with a field survey method was used to collect data of geographic coordinates of these brands using a hand-held Garmin Global Positioning System (GPS) device, these points were plotted in the geographic information systems (GIS) environment employing the 10.5 version of the software., Nearest Neighbor Analysis (NNA) statistical tool was used for the analysis. The results revealed a highly clustered distribution pattern (z-score = -19.101, Nearest Neighbor Ratio = 0.57, p-value = 0.00), indicating that brands are concentrated in specific areas rather than evenly distributed. This clustering is attributed to, economic efficiencies, and high demand in densely populated urban areas. The study recommends targeted monitoring of production areas to ensure water quality standards are met.